Vue.js 2 cookbook : build modern, interactive web applications with Vue.js - Passaglia, Andrea (Birmingham : Packt, 2017)
101 hands-on recipes that teach you how to build professional, structured web apps with Vue.js About This Book Understand and use Vue's reactivity system, data binding, and computed properties Create fluid transitions in your application with Vue's built-in transition system Use Vuex and Webpack to build medium-to-large scale SPAs and enhance your development workflow Who This Book Is For This book is for developers who want to learn about Vue.js through practical examples to quickly and efficiently build modern, interactive web applications. Prior experience and familiarity with JavaScript, HTML, and CSS are recommended as the recipes build upon that knowledge. It will also enable both new and existing Vue.js users to expand their knowledge of the framework. What You Will Learn Understand the fundamentals of Vue.js through numerous practical examples Piece together complex web interfaces using the Vue.js component system Use Webpack and Babel to enhance your development workflow Manage your application's state using Vuex and see how to structure your projects according to best practices Seamlessly implement routing in your single page applications using Vue Router Find out how to use Vue.js with a variety of technologies such as Node.js, Electron, Socket.io, Firebase, and HorizonDB by building complete applications In Detail Vue.js is an open source JavaScript library for building modern, interactive web applications. With a rapidly growing community and a strong ecosystem, Vue.js makes developing complex single page applications a breeze. Its component-based approach, intuitive API, blazing fast core, and compact size make Vue.js a great solution to craft your next front-end application. From basic to advanced recipes, this book arms you with practical solutions to common tasks when building an application using Vue. We start off by exploring the fundamentals of Vue.js: its reactivity system, data-binding syntax, and component-based architecture through practical examples. After that, we delve into integrating Webpack and Babel to enhance your development workflow using single file components. Finally, we take an in-depth look at Vuex for state management and Vue Router to route in your single page applications, and integrate a variety of technologies ranging from Node.js to Electron, and Socket.io to Firebase and HorizonDB. This book will provide you with the best practices as determined by the Vue.js community. Style and approach This book offers detailed, easy-to-follow recipes that will help you harness full potential of Vue.js. The guide will provide you with working code examples for many of the common problems that web developers face. Each recipe is designed to help you quickly understand and solve a particular problem that is commonly faced by developers using Vue.js in a simple and intuitive manner. This book also includes larger recipes to address obstacles arising from building medium-to-large scale applications with Vue.js.
Vue.js 2 cookbook : build modern, interactive web applications with Vue.js -- About the Author -- About the Reviewer -- Table of Contents -- Preface -- Chapter 1: Getting Started with Vue.js -- Chapter 2: Basic Vue.js Features -- Chapter 3: Transitions and Animations -- Chapter 4: All About Components -- Chapter 5: Vue Communicates with the Internet -- Chapter 6: Single Page Applications -- Chapter 7: Unit Testing and End-to-End Testing -- Chapter 8: Organize + Automate + Deploy = Webpack -- Chapter 9: Advanced Vue.js -- Directives, Plugins, and Render Functions -- Chapter 10: Large Application Patterns with Vuex -- Chapter 11: Integrating with Other Frameworks -- Index.
Includes index.
Specialized.
Print version record.
Added to collection customer.56279.3
Keywords: JavaScript (Computer program language); Web applications -- Programming; JavaScript (Langage de programmation); Applications Web -- Programmation; COMPUTERS -- Web -- Web Programming; COMPUTERS -- Programming Languages -- JavaScript; COMPUTERS -- Web -- General; JavaScript (Computer program language)